Active trachoma prevalence and its associated factors among children aged 1-9 years in rural residents of Lare District, Southwest Ethiopia - Yitayeh Belsti; Sofonias Addis Fekadu; Abel Sinshaw Assem (International Journal of Ophthalmology, 2021)
AIM: To determine the prevalence of active trachoma and its associated factors among children in Lare District, Southwest Ethiopia, 2019. METHODS: A community-based cross-sectional study was conducted. A total of 620 participants were recruited using a multi-stage sampling technique. A structured questionnaire, torch, and magnifying loupes were used for data collection. The data was entered into epidemiological information and exported to statistical package for social science version 20 for analysis. The bi-variable and multivariable Logistic regression analysis model was fitted to identify factors associated with active trachoma. Odds ratio with a 95%CI was used to show the direction and strength of association between independent and outcome variables. RESULTS: A total of 610 children participated in this study with a response rate of 98.39%. The prevalence of active trachoma was 132 (21.60%; 95%CI: 18.40-24.70). Family size being 6-9 (AOR=2.34; 95%CI: 1.14-5.02), presence of more than two preschool children in a house (AOR=2.04; 95%CI: 1.12-3.70), open field waste disposal system (AOR=2.62; 95%CI: 1.00-6.80) and type of latrine being uncovered (AOR=4.12; 95%CI: 2.00-8.51) were positively associated with active trachoma. On the other side, water consumption being 40-60 liters per day was a protective factor for active trachoma. CONCLUSION: The prevalence of active trachoma is high among children aged 1-9y in Lare District. Uncovered latrine, open field waste disposal system, family sizes of 6-9, and the presence of more than two preschool children in a house are associated with the occurrence of active trachoma. On the other side, water consumption of 40-60 liters is a protective factor.